Association of STAT3 Common Variations with Obesity and Hypertriglyceridemia: Protective and Contributive Effects - Ma, Zuliang; Wang, Guanghai; Chen, Xuejiao; Ou, Zejin; Zou, Fei (International journal of molecular sciences, 2014)
Signal transducer and activator of transcription 3 (STAT3) plays an important role in energy metabolism. Here we explore whether STAT3 common variations influence risks of obesity and other metabolic disorders in a Chinese Han population. Two tagging single nucleotide polymorphisms (tagSNPs), rs1053005 and rs957970, were used to capture the common variations of STAT3. Relationships between genotypes and obesity, body mass index, plasma triglyceride and other metabolic diseases related parameters were analyzed for association study in 1742 subjects. Generalized linear model and logistic regression model were used for quantitative data analysis and case-control study, respectively. rs1053005 was significantly associated with body mass index and waist circumference (p = 0.013 and p = 0.02, respectively). rs957970 was significantly associated with plasma level of triglyceride (p = 0.007). GG genotype at rs1053005 had lower risks of both general obesity and central obesity (OR = 0.40, p = 0.034; OR = 0.42, p = 0.007, respectively) compared with AA genotype. CT genotype at rs957970 had a higher risk of hypertriglyceridemia (OR = 1.43, p = 0.015) compared with TT genotype. Neither of the two SNPs was associated with othermetabolic diseases related parameters. Our observations indicated that common variations of STAT3 could significantly affect the risk of obesity and hypertriglyceridemia in Chinese Han population.